Rare patients in routine care: Treatment and outcome in advanced papillary renal cell carcinoma in the prospective German clinical RCC‐Registry. Issue 5 (22nd November 2019) - Staehler, Michael; Goebell, Peter J.; Müller, Lothar; Emde, Till‐Oliver; Wetzel, Natalie; Kruggel, Lisa; Jänicke, Martina; Marschner, Norbert; ,
Abstract : Non‐clear cell renal cell carcinoma is a very rare malignancy that includes several histological subtypes. Each subtype may need to be addressed separately regarding prognosis and treatment; however, no Phase III clinical trial data exist. Thus, treatment recommendations for patients with non‐clear cell metastatic RCC (mRCC) remain unclear. We present first prospective data on choice of first‐ and second‐line treatment in routine practice and outcome of patients with papillary mRCC. From the prospective German clinical cohort study (RCC‐Registry), 99 patients with papillary mRCC treated with systemic first‐line therapy between December 2007 and May 2017 were included. Prospectively enrolled patients who had started first‐line treatment until May 15, 2016, were included into the outcome analyses ( n = 82). Treatment was similar to therapies used for clear cell mRCC and consisted of tyrosine kinase inhibitors, mechanistic target of rapamycin inhibitors and recently checkpoint inhibitors. Median progression‐free survival from start of first‐line treatment was 5.4 months (95% confidence interval [CI], 4.1–9.2) and median overall survival was 12.0 months (95% CI, 8.1–20.0). At data cutoff, 73% of the patients died, 6% were still observed, 12% were lost to follow‐up, and 9% were alive at the end of the individual 3‐year observation period. Despite the lack of prospective Phase III evidence in patients with papillary mRCC, our real‐world data reveal effectiveness of systemic clear cell mRCC therapy in papillary mRCC. The prognosis seems to be inferior for papillary compared to clear cell mRCC. Further studies are needed to identify drivers of effectiveness of systemic therapy for papillary mRCC. Abstract : What's new? Over the past decade, the treatment landscape for locally advanced or metastatic renal cell carcinoma (mRCC) has dramatically changed. To date, however, guideline recommendations mainly address patients with clear cell mRCC, due to a lack of prospective Phase III evidence for the rarer, non‐clear cell mRCC subtypes. This is the first longitudinal, prospective cohort study evaluating treatment and survival of patients with papillary mRCC outside a prospective clinical trial setting. The presented real‐world data help bridge the evidence gap by revealing the frequent use and effectiveness of systemic clear cell mRCC therapy in papillary mRCC, with a seemingly inferior prognosis.